Pain, masticatory performance and swallowing threshold in orthodontic patients - Trein, Marcos Porto (2013)
OBJECTIVE: The aim of this study was to assess pain, masticatory performance and swallowing threshold of patients undergoing orthodontic treatment. METHODS: Ten patients of both genders (mean age of 17.25 ± 5.21 years), with complete permanent dentition, who underwent orthodontic treatment with fixed appliances were evaluated. The masticatory performance and the swallowing threshold were assessed by patient's individual capacity of fragmenting an artificial test food (Optocal) which was chewed and had the resulting particles processed by a standardized sieving method, presenting the median particle size (MPS) of crushed units. The intensity of pain / discomfort during chewing was evaluated by means of a visual analog scale. All tests were performed at the following times: T0 - before activating the orthodontic appliance; T1 - 24 hours after activation, and T2 - 30 days after activation. RESULTS: The results showed a significant increase in pain at T1 (T0 - 0.60 ± 0.70 mm; T1 - 66.2 ± 34.5 mm), returning to baseline values at T2 (3.20 ± 3.82 mm). Masticatory performance was also reduced in T1 (MPS 10.15 ± 1.1 mm²) in comparison to T0 (MPS 7.01 ± 2.9 mm²) and T2 (MPS 6.76 ± 1.3 mm²). However, particle size was not affected in the swallowing threshold test (T0 - 5.47 ± 2.37 mm²; T1 - 6.19 ± 2.05 mm²; T2 - 5.94 ± 2.36 mm²). CONCLUSION: The orthodontic appliances did not interfere in the size of the particles that would be swallowed, even in the presence of pain.